2A-DUB/Mysm1 Regulates Epidermal Development in Part by Suppressing p53-Mediated Programs - Wilms, Christina; Krikki, Ioanna; Hainzl, Adelheid; Kilo, Sonja; Alupei, Marius; Makrantonaki, Evgenia; Wagner, Maximilian; Kroeger, Carsten M.; Brinker, Titus Josef; Gatzka, Martina (International Journal of Molecular Sciences, 2018)
Development and homeostasis of the epidermis are governed by a complex network of sequence-specific transcription factors and epigenetic modifiers cooperatively regulating the subtle balance of progenitor cell self-renewal and terminal differentiation. To investigate the role of histone H2A deubiquitinase 2A-DUB/Mysm1 in the skin, we systematically analyzed expression, developmental functions, and potential interactions of this epigenetic regulator using Mysm1-deficient mice and skin-derived epidermal cells. Morphologically, skin of newborn and young adult Mysm1-deficient mice was atrophic with reduced thickness and cellularity of epidermis, dermis, and subcutis, in context with altered barrier function. Skin atrophy correlated with reduced proliferation rates in Mysm1-/- epidermis and hair follicles, and increased apoptosis compared with wild-type controls, along with increases in DNA-damage marker γH2AX. In accordance with diminished α6-Integrinhigh+CD34⁺ epidermal stem cells, reduced colony formation of Mysm1-/- epidermal progenitors was detectable in vitro. On the molecular level, we identified p53 as potential mediator of the defective Mysm1-deficient epidermal compartment, resulting in increased pro-apoptotic and anti-proliferative gene expression. In Mysm1-/-p53-/- double-deficient mice, significant recovery of skin atrophy was observed. Functional properties of Mysm1-/- developing epidermis were assessed by quantifying the transepidermal water loss. In summary, this investigation uncovers a role for 2A-DUB/Mysm1 in suppression of p53-mediated inhibitory programs during epidermal development.
EVALuna2:34906

707 Dermal absorption of fluoride and hydrogen ions following topical exposure to hydrofluoric acid - Kilo, Sonja; Dennerlein, Kathrin; Korinth, Gintautas; Göen, Thomas; Drexler, Hans (Occupational and Environmental Medicine 2018, 2018)
Introduction Despite being an extremely hazardous liquid, hydrofluoric acid (HF) is commonly used in industry due to its unique chemical properties. Chemically HF is defined as a ‘weak’ acid but fluoride ions can induce serious systemic toxic effects. Upon contact with low concentrated HF, symptoms such as pain or local lesions may be delayed. The aim of this study was to characterise changes in intradermal pH and dermal fluoride penetration following HF application. Methods A static diffusion cell model was used to study dermal fluoride penetration for 6–72 hour following application of varying amounts of HF (c=5%–50%, 100–160 µl/0.64cm2, 1–10 min.) on human skin (thickness 0.9 or 2.5 mm). Intra- and transdermal amounts of fluoride and intradermal pH were determined. Result Transdermal penetration of fluoride increased exponentially with increasing HF concentration. In addition, penetration increased four-times by extending the exposure time from 1 to 3 min. No further increase was seen with longer HF application (5 and 10 min.). The increased amount of HF penetrated through 0.9 mm compared to 2.5 mm skin within one hour was levelled out at later time points. Intradermal accumulation of fluoride increased dose-dependently but to a lower degree. Intradermal pH dropped with increasing HF concentration and exposure time. Additionally, the lag time between HF application and onset of pH changes decreased with increasing HF concentration and application time. Discussion The results of the present study show that following 3 min. HF application maximal amounts of fluorides seem to have penetrated the skin. The longer lag time in pH drop with lower concentrated HF might explain the delay between HF contact and onset of pai

914 Hydrofluoric acid – effects of skin decontamination on the bioavailability of fluoride - Dennerlein, Kathrin; Hahn, Theresa; Göen, Thomas; Drexler, Hans; Kilo, Sonja (2018)
Introduction After dermal contact to occupational hazardous substances the cleaning of exposed skin areas is an important first aid measure to reduce adverse health effects. Due to possible severe systemic intoxication following dermal exposure to hydrofluoric acid (HF) the decontamination of skin should focus on the inactivation of free fluoride ions. The present ex-vivo study investigated the effects of exposure duration and different antidotes on the potential systemic uptake of fluoride. Methods The transdermal penetration of HF (c=30%) through excised human skin was investigated by using static diffusion cells. After dermal application of the acid (100 µl/0.64 cm2) for 1 min the excess was removed using one dry cotton swab. Subsequently, the skin was cleaned with water, calcium gluconate (CaGl), polyethylene glycol (PEG) 400 or hexafluorine© using a standardised protocol. In a further study, the application time was extended to 3 min to assess the effect of exposure duration. Chemical analyses of fluoride were carried out by GC-MS or via a fluoride-sensitive electrode. Result Extension of the exposure time from 1 to 3 min led to an enhancement in the transdermal penetration of fluoride, however with similar penetration kinetics. At the end of experiments (6 hour) a 7–fold higher fluoride amount was detected in the receptor fluid (16 vs 114 µg). In all test series maximum flux was achieved within the first hour past exposure. Decontamination of the skin reduced the cumulative penetrated amount of fluoride by 28% (PEG 400), 49% (water) and 64% (CaGl/hexafluorine©) compared to control. Discussion The results indicate that the systemic uptake of fluoride ions and therefore possible systemic intoxication after exposure to hydrofluoric acid can be diminished by shortening the exposure duration. Reduction was further increased by decontamination of skin – most by substances which are known to supply the complexation of fluoride ion

A chemical and physical assessment of small nerve fiber function in diabetes mellitus - Berghoff, Martin; Kilo, Sonja; Freeman, Roy L. (2005)

Attenuation of peripheral inflammation by nicotine: Comparison of neuropeptide secretion and behavioral responses in the rat. - Kilo, Sonja; Hargreaves, Ken M; Flores, Christopher M. (1997)

Calcium, magnesium and aluminium ions as decontaminating agents against dermal fluoride absorption following hydrofluoric acid exposure - Mini Vijayan, Suvarna; Göen, Thomas; Dennerlein, Kathrin; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology in Vitro, 2021)
The fluoride ions of the industrially largely irreplaceable, locally corrosive hydrofluoric acid (HF) can scavenge cations in biological tissues, which explains their high toxic potential, and also leads to local acidification through proton release. The influence of three complexing agents, calcium (Ca2+) gluconate (as 2.5% Ca2+gel and individually (2.84%) or commercially (10%) formulated Ca2+solution), magnesium (Mg2+) gluconate (2.84%) solution and aluminium (Al3+) solution (Hexafluorine®, pure and diluted) on the absorption of fluoride following HF exposure (1–3 min, 100 μl, 30%/0.64 cm2) through human skin was investigated in an ex-vivo diffusion cell model. Fluoride absorption was assessed over 6–24 h and analysed with a fluoride electrode. Decreasing the contamination time reduced the fluoride absorption distinctly which was further reduced by the application of fluoride-binding decontamination agents (Ca2+, Mg2+, Al3+) or water alone without being significantly different. Ca2+ appeared slightly more effective than Mg2+ in reducing fluoride absorption. Moreover, the addition of pH adjusting buffer promoted the decontamination efficacy. Fluoride-binding agents can facilitate the decontamination of dermal HF exposure. However, prompt decontamination appeared to be the key to successful limitation of fluoride absorption and pushes the choice of decontamination agent almost into the background.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Aluminium; Calcium gluconate; Decontamination; Fluoride absorption; Human skin; Hydrofluoric acid

Cannabinoids reduce hyperalgesia and inflammation via interaction with peripheral CB1 receptors - Kilo, Sonja; Hargreaves, Ken M; Richardson, Jennelle D. (Pain, 1998)
Central antinociceptive effects of cannabinoids have been well documented. However, relatively little is known about the peripheral effects of the cannabinoids on inflammation, In the present study, we evaluated the effects of peripherally administered cannabinoids on three indices of inflammation: carrageenan-induced thermal hyperalgesia, carrageenan-induced edema, and capsaicin-induced plasma extravasation. In addition, we determined the effect of cannabinoids on capsaicin-evoked neuropeptide release from isolated rat hindpaw skin. Our results indicate that cannabinoids produce antihyperalgesia via interaction with a peripheral CBI receptor. Peripheral, but not systemic, administration of 0.01 ng anandamide inhibited the induction of hyperalgesia. Peripheral administration of anandamide also attenuated hyperalgesia after its development via interaction with the CBI cannabinoid receptor subtype as indicated by its reversal with the CBI receptor antagonist SR 141716A. Additionally, peripheral, but not systemic, administration of 0.01 ng anandamide inhibited edema. Peripherally administered cannabinoids also interacted with CBI receptors to inhibit capsaicin-evoked plasma extravasation into the hindpaw. One potential mechanism for the anti-inflammatory actions of the cannabinoids is the inhibition of neurosecretion from the peripheral terminals of nociceptive primary afferent fibers. This hypothesis is supported by the finding that anandamide inhibited capsaicin-evoked release of calcitonin gene-related peptide from isolated hindpaw skin. Collectively, these results indicate that cannabinoids reduce inflammation via interaction with a peripheral CBI receptor. A potential mechanism for this effect is the inhibition of neurosecretion from capsaicin-sensitive primary afferent fibers. (C) 1998 International Association for the Study of Pain. Published by Elsevier Science B.V.
Keywords: cannabinoid; peripheral; hyperalgesia; capsaicin; neurotransmitter release; carrageenan

Capsaicin-evoked CGRP release from rat buccal mucosa: development of a model system for studying trigeminal mechanisms of neurogenic inflammation - Flores, Christopher M.; Leong, Anthony S; Dussor, Gregory O; Harding-Rose, Catherine; Hargreaves, Ken M; Kilo, Sonja (European Journal of Neuroscience, 2001)
Many of the physiological hallmarks associated with neurogenic inflammatory processes in cutaneous tissues are similarly present within orofacial structures. Such attributes include the dependence upon capsalcin-sensitive sensory neurons and the involvement of certain inflammatory mediators derived therein, including calcitonin gene-related peptide (CGRP). However, there are also important differences between the trigeminal and spinal nervous systems, and the potential contributions of neurogenic processes to inflammatory disease within the trigeminal system have yet to be fully elucidated. We present here a model system that affords the ability to study mechanisms regulating the efferent functions of peptidergic terminals that may subserve neurogenic inflammation within the oral cavity. Freshly dissected buccal mucosa tissue from adult, male, Sprague-Dawley rats was placed into chambers and superfused with oxygenated, Krebs buffer. Serial aliquots of the egressing superfusate were acquired and analysed by radioimmunoassay for immunoreactive CGRP (iCGRP). Addition of the selective excitotoxin, capsaicin (10-300 muM), to the superfusion buffer resulted in a significant, concentration-dependent increase in superfusater levels of iCGRP. Similarly, release of iCGRP from the buccal mucosa could also be evoked by a depolarizing concentration of potassium chloride (50 mm) or by the calcium ionophore A23187 (1 muM). The specific, capsaicin receptor antagonist, capsazepine (300 muM), completely abolished the capsaicin-evoked release of ICGRP while having no effect whatsoever on the potassium-evoked release. Moreover, capsaicin-evoked release was dependent upon the presence of extracellular calcium ions and was significantly, though incompletely, attenuated by neonatal capsaicin denervation. Collectively, these data indicate that the evoked neurosecretion of iCGRP in response to capsaicin occurs via a vanilloid receptor-mediated, exocytotic mechanism. The model system described here should greatly facilitate future investigations designed to identify and characterize the stimuli that regulate the release of CGRP or other neurosecretory substances in isolated tissues. This system may also be used to elucidate the role of these mediators in the aetiology of inflammatory processes within the trigeminal field of innervation.
Keywords: exocytosis; in vitro superfusion; neuropeptide; nociceptor; pain; sensory neuron

Cross-sectional study on N,N-dimethylformamide (DMF); effects on liver and alcohol intolerance - Kilo, Sonja; Göen, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
There are still concerns regarding occupational exposure to hepatotoxic DMF. This study was designed to evaluate possible liver damaging effects of DMF under current workplace conditions in synthetic fibres industries.Among other laboratory parameters, liver function parameters (alkaline phosphatase (ALP), aspartate aminotransferase, alanine aminotransferase and gamma-glutamyltransferase), the mean corpuscular erythrocyte volume (MCV) and carbohydrate-deficient transferrin (CDT) of the workforce of two companies present at the days of study were investigated. Internal exposure to DMF was assessed via three different biomarkers [sum of N-methylformamide and N-hydroxymethyl-N-methylformamide, N-acetyl-S-(N-carbamoyl)cysteine (AMCC) and 3-methyl-5-isopropylhydantoin (MIH)]. Alcohol consumption was assessed by means of direct ethanol metabolites (ethylglucuronide and ethylsulfate).None of the tested liver enzyme activities showed a positive association with any of the three exposure markers, nor did CDT and MCV. CDT was negatively associated with AMCC and the ALP activity negatively with all three exposure markers. Changes in liver function are seen mainly in conjunction with ethanol consumption but also with increasing body weight and age. MCV was associated with smoking. Almost half of the workers stated to experience alcohol flush reaction.The present study indicates that long-term exposure to DMF, which was specified by median urinary AMCC levels of 4.84 mg/g creatinine and DMF haemoglobin adduct levels of 60.5 nmol/MIH/g globin, respectively, does not result in any adverse liver effects. In contrast, these DMF exposure levels still elicit certain alcohol intolerance reactions.
EVALuna2:9751

Dermal absorption and skin damage following hydrofluoric acid exposure in an ex vivo human skin model - Dennerlein, Kathrin; Kiesewetter, Franklin; Kilo, Sonja; Jäger, Thomas; Göen, Thomas; Korinth, Gintautas; Drexler, Hans (Toxicology Letters, 2016)
The wide industrial use of hydrofluoric acid (HF) poses a high risk for accidental dermal exposure. Despite local and systemic hazards associated with HF, information on percutaneous penetration and tissue damage is rare. In the present ex vivo study, the dermal absorption of HF (detected in terms of fluoride ions) was quantified and the skin damaging potential as a function of concentration and exposure duration was assessed. Percutaneous penetration of HF (c=5, 30, and 50%) at 3 exposure durations (3, 5, and 10min) was investigated in a static diffusion cell model using freshly excised human skin. Alterations of skin were histologically evaluated. HF rapidly penetrated through skin under formation of a considerable intradermal reservoir ( 13-67% of total absorbed fluoride). Histologically, epidermal alterations were detected already after exposure to 5% HF for 3min. The degree of skin damage increased with rising concentration and exposure duration leading to coagulation necrosis. For HF concentrations of >=30%, skin damage progressed into deeper skin layers. Topically applied HF concentration was the principal parameter determining HF induced skin effects. The intradermal HF retention capacity associated with progression and prolongation of HF induced skin effects must be considered in the review of skin decontamination procedures.
EVALuna2:9745

Dermal penetration and resorption of beta-naphthylamine and N-phenyl-beta-naphthylamine from lubricants in an ex vivo human skin model - Dennerlein, Kathrin; Göen, Thomas; Zobel, Melanie; Boos, Anja; Drexler, Hans; Kilo, Sonja (Chemosphere, 2017)
Dermal Penetration of aromatic amines (AA's), often suspected or known to be carcinogenic, can play an important role in the overall human exposure. However, information on penetration of certain AA's is poor and inconsistent. Penetration of the former lubricant additive N-phenyl-beta-naphthylamine (PBNA) and its contaminant beta-naphthylamine (BNA) a known carcinogen was investigated and the influence of formulation and co-application characterized. Percutaneous penetration of BNA and PBNA through freshly excised human skin (n = 8; 48 h) was investigated using an ex vivo diffusion cell model. Both AA's were applied in a technical-conform lubricant or dissolved in hexane. The amount of BNA and PBNA applied to skin was 0.52 and 259 ?g/0.64 cm2. The analytical determination of AA's was performed by GC-MS. Both, BNA and PBNA penetrated through human skin (38 vs. 5% of applied dose). In contrast to BNA, the percutaneous penetration of PBNA continued beyond the end of exposure. Co-exposure of both AA's increased the intradermal uptake of BNA and PBNA (p < 0.05). Exposure in lubricant showed the least overall penetration (2.9 and 1.9% of applied dose). The results clearly reveal that dermal penetration of both AA's depends strongly on the mode of application. Co-application and formulation alters the penetration of the AA's.
EVALuna2:9769

Differential impairment of the sudomotor and nociceptor axon-reflex in diabetic peripheral neuropathy - Berghoff, Martin; Kilo, Sonja; Hilz, Max-Josef; Freeman, Roy L. (2006)
It is not known whether C-fiber functional subclasses are differentially affected by diabetes mellitus or whether the patterns of C-fiber dysfunction are different between type 1 and type 2 diabetes. We therefore examined efferent sympathetic sudomotor and primary afferent nociceptor C-fiber function in diabetic patients. Acetylcholine (10%) was used to evoke C-fiber (axon-reflex)-mediated responses. The nociceptor (flare) response was measured using a laser Doppler device. The sudomotor response was quantified with silastic imprints. The nociceptor C-fiber-mediated flare response was reduced in type 2 diabetic patients (P < 0.008) but was similar to controls in type 1 diabetic patients. The sympathetic C-fiber-mediated responses, including sweat volume (P < 0.05) and the number of activated sweat glands (P = 0.003), were increased in patients with type 1 diabetes. There also was a trend toward a larger axon-reflex sweat area in patients with type 1 diabetes (P = 0.09). No differences in these sweat responses were found in patients with type 2 diabetes compared to controls. These findings suggest that the functional abnormalities in diabetic peripheral neuropathy are not homogeneous and that C-fiber subclasses are differentially affected in type 1 and 2 diabetes mellitus.
Keywords: autonomic function; axon-reflex; c-fiber; diabetes; dysautonomia; laser Doppler flowmetry; silastic imprint method

DIFFERENT PATTERNS OF HYPERALGESIA INDUCED BY EXPERIMENTAL INFLAMMATION IN HUMAN SKIN - Kilo, Sonja; Schmelz, Martin; Koltzenburg, Martin; Handwerker, Hermann Otto (Brain, 1994)
Different types of hyperalgesia were studied after experimental induction of inflammation in small skin areas of healthy volunteers either by topical application of capsaicin solution (1% in 70% ethanol) or by briefly freezing a skin area of similar size to -28 degrees C. Sensory tests were performed 30 min after capsaicin application and 22 h after freeze lesions. Heat pain thresholds were lowered after both treatments, probably due to nociceptor sensitization. Hyperalgesia to four types of mechanical stimulation was studied (i) Hyperalgesia to punctate stimuli was encountered at the skin site directly affected by the noxious chemical or freeze stimulus (1 degrees zone) and in the surrounding skin (2 degrees zone) in both models though the area of 2 degrees hyperalgesia to punctate stimuli after freezing was smaller than after capsaicin. (ii) Hyperalgesia to gently blushing the skin was prominent after capsaicin in 1 degrees and 2 degrees zone, but almost absent after freezing. It was concluded that both hyperalgesia to punctate stimuli and brush-evoked pain are due to central nervous plasticity changes rather than nociceptor sensitization. As revealed by differential nerve blocks, brush-evoked pain is mediated by low threshold mechanosensitive A beta-fibres, whilst hyperalgesia to punctate stimuli can be elicited when only C-fibres conduct. in contrast to hyperalgesia to punctate stimuli it requires continuous background discharges in nociceptor units. (iii) Pressure hyperalgesia to tonic stimulation with a blunt probe was encountered in the 1 degrees zone of both types of inflammation and is probably due to recruitment of sensitized nociceptor units. (iv) Impact hyperalgesia was studied by shooting small bullets against the skin at predetermined velocities. It was found in the 1 degrees zone after freezing and absent in the capsaicin model. Differential nerve blocks revealed that it is probably mediated by sensitized C-fibres. in conclusion, different types of inflammatory changes may result in characteristic different patterns of hyperalgesia.
Keywords: PAIN; C-FIBERS; A-FIBERS; NOCICEPTION; SENSITIZATION

Effect of Skin Protection and Skin Irritation on the Internal Exposure to Carbon Disulfide in Employees of the Viscose Industry - Kilo, Sonja; Zonnur, Nina; Uter, Wolfgang; Göen, Thomas; Drexler, Hans (Annals of Occupational Hygiene, 2015)
Occupational exposure to carbon disulfide (CS2) leads to inhalative and dermal uptake and thereby to internal exposure. In order to prevent occupational contact dermatitis, gloves and skin protection creams are used at the workplace. The aim of the study was the evaluation of the influence of personal skin protection and irritation on the internal exposure to CS2 of employees in the viscose industry.One hundred and eighty-two male CS2-exposed employees were included in the study and were examined regarding working conditions, use of personal protective measures und skin status. Personal air monitoring and biological monitoring was performed and the 'relative internal exposure' (RIE, internal exposure in relation to external exposure) calculated. A multiple regression analysis calculated the influence of skin protection and irritation on CS2 uptake.Usage of skin protection creams and gloves (and both in combination) while working was associated with a significantly higher RIE indicating a higher dermal penetration of CS2. Equally, irritated skin and younger age was associated with a higher internal burden.Gloves and skin protection creams are useful for preventing occupational skin diseases. However, when handling skin-resorptive substances like CS2, they can increase internal exposure or skin irritation. Therefore, we recommend the careful consideration of benefits and risks of protective creams and gloves at the workplace.
EVALuna2:5491

Evaluation of biomarkers assessing regular alcohol consumption in an occupational setting - Kilo, Sonja; Hofmann, Birgit; Eckert, Elisabeth; Göen, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
An estimation of ethanol intake is frequently of importance in the frame work of studies, but not trivial to achieve. Problems are "underreporting", a very short time frame for the detection of ethanol as direct marker and interference of many in- and outside body factors with strain parameters. The aim of this study was to explore the suitability of the direct urinary biomarkers ethyl glucuronide (EtG) and ethyl sulphate (EtS) to assess moderate but regular alcohol consumption.A total of 175 male workers without any known occupational contact to substances influencing liver functions or metabolism of ethanol were examined. Strain parameters of alcohol consumption, i.e. the liver function tests (LFTs: aspartate aminotransferase, alanine aminotransferase, gamma-glutamyltransferase), carbohydrate-deficient transferrin (CDT), mean corpuscular erythrocyte volume (MCV) and the markers of alcohol consumption (EtG and EtS) have been analysed and compared.Up to 14 % of workers had been outside reference range for strain parameters. 62.3 % of the workers had at least traceable amounts of EtG and 84.6 % of EtS. Values above cut-off (indicating voluntary ethanol intake) were found in 34.9 and 51.4 % of the workers for EtG and EtS, respectively. In multiple linear regression analyses, CDT and MCV but not the LFTs showed a dependency from the non-oxidative ethanol metabolites. The LFTs were influenced by BMI.Determination of EtG and EtS in urine is an adequate tool to assess moderate but regular alcohol consumption.
EVALuna2:9752

Evaluation of nociceptive C-fiber function in diabetic peripheral neuropathy - Berghoff, Martin; Kilo, Sonja; Hilz, Max-Josef; Freeman, Roy L. (2002)

Evaluation of the effect of skin cleaning procedures on the dermal absorption of chemicals - Dennerlein, Kathrin; Jäger, Thomas; Göen, Thomas; Kilo, Sonja; Schaller, Karl-Heinz; Drexler, Hans; Korinth, Gintautas (Toxicology in Vitro, 2015)
To reduce the internal exposure, skin decontamination is the most important measure after dermal contact to chemicals. However, no harmonized skin cleaning procedure for experimental ex vivo studies is published. In our study, the impact of two skin cleaning techniques on dermal penetration kinetics and intradermal deposition of 1,4-dioxane, 5% hydrofluoric acid (HF, detected in terms of fluoride ions), and anisole was evaluated to develop a reliable ex vivo skin cleaning method using the diffusion cell technique. After exposure (duration: 3 min (HF); 1h (1,4-dioxane and anisole)) of excised human skin (n=6-8) decontamination was performed by (I) water-soaked cotton swabs or (II) direct application of water on the exposure area. The effect of skin cleaning was investigated by analysing the concentration time course of chemicals in the receptor fluid of diffusion cells and by determining the deposition in skin. Both skin cleaning procedures reduced the amount of fluoride in the skin compartments (p<0.05) and the receptor fluid (p<0.1). However, the effect of cleaning on the dermal absorption of the organic test compounds was not significant. The results demonstrate the suitability of the applied ex vivo protocol for investigating the effectiveness of skin cleaning measures following dermal exposure. In addition, data reveal that the determination of test compounds in both, skin compartments as well as receptor fluid as equivalent for the systemic uptake needs to be considered in studies assessing the effectiveness of skin decontamination procedures.
EVALuna2:9730

Exposure of the German general population to platinum and rhodium - Urinary levels and determining factors - Munker, Sven; Kilo, Sonja; Roess, Christoph; Jeitner, Peter; Schierl, Rudolf; Göen, Thomas; Drexler, Hans (International Journal of Hygiene and Environmental Health, 2016)
In this study the exposure of the general population in Germany to platinum and rhodium and its determinants was investigated in 259 participants (subdivided in three groups) by urine analyses and assessment of the dental status. Complementary, an interview including questions characterising possible exposure to traffic exhaust was conducted. The median excretion was 2.42ng platinum/g creatinine and 7.27ng rhodium/g creatinine. The detailed analysis of the collected data showed significant higher platinum excretion values with increasing number of surfaces covered with restorations containing precious metals (R=0.389; p<0.001), but also higher values for habitants of urban areas (median=3.43ng/g creatinine; 95th percentile=25.2ng/g) compared with those of rural areas (median=2.06ng/g creatinine; 95th percentile=20.0ng/g). Also, participants working in urban areas showed higher platinum excretion values (median=3.27ng/g; 95th percentile=19.6ng/g). Male participants living and working next to highly frequented roads showed higher rhodium excretion values (median=7.27ng/g; 95th percentile=13.5 ng/g). In summary, the study showed that exhaust emissions have an influence on platinum and rhodium excretion, but for platinum this influence is rather low compared to the influence of precious metals containing restorations.
EVALuna2:9750

Hautabsorption - Kilo, Sonja (Umweltmedizin, 2017)

Impact of physiologically relevant temperatures on dermal absorption of active substances - an ex-vivo study in human skin - Kilo, Sonja; Wick, J.; Mini Vijayan, Suvarna; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans (Toxicology in Vitro, 2020)
Skin temperature plays a certain role in the dermal absorption of substances, but the extent and mechanisms of skin temperatures-induced modulation in ranges caused by physiological thermoregulation or environmental conditions are largely unknown. The influence of dermal temperature on the absorption of the model lipophilic compound (anisole) and the model hydrophilic compounds (1,4-dioxane, ethanol) through human skin was investigated at three dermal temperatures (25, 32 and 39 °C) in an ex-vivo diffusion cell model. The substances were applied to the skin and transdermal penetration was monitored. All substances showed temperature dependent variations in their penetration behavior (3 h: 25–39 °C: 202–275% increase in cumulative, transdermally penetrated amounts). The relative differences in absorption in relation to temperature were greatest within 45 min after exposure (25–39 °C: 347–653% rise in cumulated penetration), although absolute amounts absorbed were small (45 min vs. 3 h: 4.5–14.5%). Regardless of blood circulation, skin temperature significantly influences the amount and kinetics of dermal absorption. Substance-dependent, temperature-related changes of the lipid layer order or the porous pathway may facilitate penetration. The early-stage modulation of transdermal penetration indicates transappendageal absorption, which may be relevant for short-term exposures. For both, toxicological evaluation and perfusion cell studies, it is important to consider the thermal influence on absorption or to perform the latter at a standardized temperature (32±1 °C).
CRIS-Team Scopus Importer:2020-09-11
Keywords: Dermal absorption; Diffusion cell; Influence of temperature; Transdermal penetration

Impact of skin temperature and intradermal pH on transdermal fluoride absorption following hydrofluoric acid exposure: An ex vivo diffusion cell study in human skin - Mini Vijayan, Suvarna; Wolfschmidt, Anna; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology Letters, 2025)
Accidents involving hydrofluoric acid (HF) can cause systemic poisoning due to the transdermal absorption of fluoride ions. The present study investigates the impact of skin temperature and intradermal pH on fluoride absorption and its kinetics. Human skin was exposed to 30 % HF for 3 minutes using a static diffusion cell model. The study compared cumulative fluoride absorption at two different skin temperatures (24°C and 32°C) and two intradermal pH values (6.5 and 7.2). Experiments were performed at least three times per treatment and per donor (n = 5), over a duration of 8 h and 12 h for pH and temperature experiments, respectively. Results showed that fluoride absorption increased with temperature, with a ∼17.8 % increase in cumulative penetration at 32°C compared to 24°C. The maximum flux rate through the skin was reached within the first hour and was ∼54 % lower at 24°C. Additionally, acidifying the skin to an intradermal pH of 6.5 led to a significant increase in cumulative fluoride absorption by ∼12.6 % and a ∼50.3 % increase in the maximum flux rate. The findings suggest that reducing fluoride absorption after accidental skin contact with HF may be achieved by lowering skin temperature and buffering intradermal pH to a physiological level. These results have important implications for first-aid measures in real-life scenarios involving HF exposure. Controlling skin temperature by cooling and intradermal pH with the addition of buffering agents may enhance decontamination strategies.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Clinical significance; Ex Vivo human skin; Franz Diffusion cell; Hydrofluoric acid; Intradermal pH; Skin temperature; Transdermal fluoride absorption

Impaired endothelium dependent with preserved non-endothelium dependent cutaneous microvascular function in patients with insulin dependent diabetes mellitus - Kilo, Sonja; Khalil, Lauren A.; Veves, Aristidis; Hilz, Max-Josef; Freeman, Roy L. (1998)

INFLAMMATORY MODELS OF CUTANEOUS HYPERALGESIA ARE SENSITIVE TO EFFECTS OF IBUPROFEN IN MAN - Kilo, Sonja; Forster, Clemens; Geisslinger, Gerd; Brune, Kay; Handwerker, Hermann Otto (Pain, 1995)
A new experimental procedure was developed to quantify the analgesic actions of non-steroidal anti-inflammatory drugs (NSAIDs) in healthy human subjects. In order to mimic the clinical situation, the drug was 'therapeutically' administered 1 day after induction of inflammation by freezing a small skin area. The procedure was easily tolerated and led to a marked hyperalgesia without ongoing pain which was tested using mechanical impact stimulation and magnitude estimation. For comparison, we used a previously established model of repeated noxious pinching of an interdigital skin web which induces a hyperalgesia to pressure (rated via visual analogue scale), and topical application of capsaicin which leads to quantifiable flare and allodynia responses. The effects of a cumulative drug regime of ibuprofen in 2 different doses (3 x 400 mg and 3 x 800 mg at 2-h intervals) were tested versus placebo using a double-blind cross-over design with 24 volunteers of either gender. Ibuprofen caused a significant suppression of the hyperalgesia to repeated pinching and of the hyperalgesia to impact stimulation following freeze trauma. In contrast, there was no effect on the areas of flare and allodynia induced by capsaicin application and on the impact evoked sensations from untreated skin. The two dosages of ibuprofen, however, appeared to be equally effective in a way that suggests a plateauing of the antihyperalgesic effect. The two models in which hyperalgesia is affected by ibuprofen, i.e., repeated pinching and impact stimulation after freeze trauma, seem to provide comparable sensitivity. The freeze model may in the future have the advantage to allow for a better temporal resolution of the drug's action profile.
Keywords: NONSTEROIDAL ANTIINFLAMMATORY DRUG; PAIN; EXPERIMENTAL; NOCICEPTION; PERIPHERAL ANALGESIA; (HUMAN)

Influence of Ibuprofen on Pain from physically induced Inflammation in human skin - Kilo, Sonja; Forster, Clemens; Menzel, Sabine; Handwerker, Hermann Otto; Brune, Kay (Naunyn-Schmiedeberg's Archives of Pharmacology, 1994)

Intradermal and transdermal absorption of beta-naphthylamine and N-Phenyl-beta-naphthylamine in a viable human skin model - Mini Vijayan, Suvarna; Baierl, Moritz; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology in Vitro, 2024)
Technical products containing N-Phenyl-beta-naphthylamine (PBNA) are contaminated with beta-naphthylamine (BNA), a known carcinogen. Both amines penetrate the skin to different degrees, but little is known about their dermal-depot formation. This study investigated the dermal penetration of PBNA and its degradation product BNA using a viable human-skin model. PBNA (259 μg) or BNA (0.52 μg) in n-hexane and industrial grease were applied to freshly excised human skin (n = 6, 0.64 cm2) for 2-72 h. After temporary/continuous and single/repeated exposure, samples were taken (stratum corneum, epidermis/dermis, receptor fluid) and analyzed for their amine content by GC–MS. Continuous exposure led to a PBNA dermal depot of ∼47 μg/cm2 over 72 h. Temporary applications also resulted in lower but consistent PBNA dermal depots. A single 2-h application resulted in a dermal depot of ∼16 μg/cm2 after 72 h, while this was ∼25 μg/0.64 cm2 with repeated applications. BNA behaved differently; with repeated 2-h applications, intradermally retained BNA initially increased 3–6 fold, then dropped to ∼200–250 ng/cm2. This incomplete decline upon repeated short-term exposure to PBNA suggests that a BNA dermal depot is formed either due to contamination of PBNA with BNA or to enzymatic conversion of PBNA to BNA. Additionally, PBNA dermal depots were saturable under the given conditions. These findings highlight the importance of understanding the dermal-exposure dynamics of potential carcinogenic compounds in industrial settings.
CRIS-Team Scopus Importer:2024-10-18
Keywords: beta-naphthylamine; Dermal depot; Intradermal penetration; N-Phenyl-beta-naphthylamine; Transdermal absorption; Viable skin

Investigation of the neural and vascular control mechanisms of the cutaneous microcirculation - Berghoff, Martin; Kilo, Sonja; Hilz, Max-Josef; Freeman, Roy L. (1999)

Investigation of the relationship between the adrenergic vasoconstrictor system, cholinergic vasodilatation, and gender - Berghoff, Martin; Kathpal, Madeera; Kilo, Sonja; Hilz, Max-Josef; Freeman, Roy L. (2000)

Neural and endothelial control of the microcirculation in diabetic peripheral neuropathy - Kilo, Sonja; Berghoff, Martin; Hilz, Max-Josef; Freeman, Roy L. (Neurology, 2000)
Objective: To examine the role played by endothelium-dependent and endothelium-independent vasodilation of the cutaneous microcirculation and their relationship to neural microcirculatory control in type 1 and type 2 diabetic patients. Methods: Acetylcholine and sodium nitroprusside were iontophoresed using a dose-response technique. Endothelium-dependent, endothelium-independent, and C-fiber-mediated vasodilation were measured with a laser Doppler device. Results: Endothelium-dependent vasodilation of the forearm cutaneous microcirculation was attenuated in diabetic subjects. The response was less in type 2 diabetic subjects than in controls (p < 0.005). In contrast, there was no significant difference between type 1 diabetic subjects and controls. There was no significant abnormality in endothelium-independent vasodilation in either diabetic group. The C-fiber-mediated axon reflex in the forearm was impaired in both type 1 and type 2 diabetics, which is consistent with a small-fiber neuropathy (p < 0.005). The duration of diabetes in type 2 diabetics was a significant predictor of the maximum endothelium-mediated vasodilation. Conclusion: Changes in cutaneous blood flow are seen relatively early in the course of diabetic peripheral neuropathy and are characterized by endothelial and neural but not smooth muscle dysfunction. The presence of significant C-fiber impairment in both diabetic groups, together with significantly greater dysfunction in endothelium-dependent vasodilation in type 2 diabetics, suggests that the endothelial function and nitric oxide may play a greater role in the pathogenesis of diabetic peripheral neuropathy in type 2 diabetic patients.
Keywords: diabetic neuropathy; nitric oxide; endothelium; axon reflex

Neuronal nicotinic receptor expression in sensory neurons of the rat trigeminal ganglion: Demonstration of alpha 3 beta 4, a novel subtype in the mammalian nervous system - Flores, Christopher M.; DeCamp, Raquel M.; Kilo, Sonja; Rogers, Scott W.; Hargreaves, Ken M (Journal of Neuroscience, 1996)
The identification of a family of neuronal nicotinic receptor subunit genes establishes the potential for multiple subtypes with diverse physiological functions. Virtually all of the high affinity nicotinic receptors measured to date in the rodent CNS are composed of alpha 4 and beta 2 subunits only. However, the demonstration of other subunit transcripts in a variety of central and peripheral nervous tissues suggests a greater degree of receptor subtype heterogeneity than so far has been elucidated. The purpose of the present studies was to determine at the mRNA and protein levels which neuronal nicotinic receptor subunits are expressed by sensory neurons of the rat trigeminal ganglion and in what combinations these gene products associate to form neuronal nicotinic receptor subtypes in this tissue. Radioreceptor binding analysis indicated that in the adult rat trigeminal ganglion there exist at least two nicotinic receptor binding sites with differing affinities for [H-3]-epibatidine. In situ hybridization histochemical studies revealed the existence of mRNA encoding the alpha 3, alpha 4, alpha 5, beta 2, and beta 4 subunits, but not the alpha 2 subunit. Immunoprecipitation with subunit-specific antisera demonstrated that each of the subunits present in the ganglion at the mRNA level is a constituent of nicotinic receptors capable of binding H-3-epibatidine. Various applications of these approaches yielded strong evidence that, in addition to alpha 4 beta 2, which is thought to be the predominant neuronal nicotinic receptor subtype in the rodent CNS, trigeminal sensory neurons express as the principal subtype alpha 3 beta 4, which has not been demonstrated previously in mammalian nervous tissue.
Keywords: nicotinic receptor subtype; sensory neurons; trigeminal ganglion; radioreceptor binding; [H-3]-epibatidine; immunoprecipitation; subunit composition; in situ hybridization; mRNA

Peripheral CGRP release as a marker for neurogenic inflammation: a model system for the study of neuropeptide secretion in rat paw skin - Kilo, Sonja; Harding-Rose, Catherine; Hargreaves, Ken M; Flores, Christopher M. (Pain, 1997)
The local release of pro-inflammatory neuropeptides in the periphery has been associated with the development of neurogenic inflammation. However, there is an increasing number of reports demonstrating tissue-dependent differences regarding the mechanisms engaged by these neuropeptides to initiate and maintain the inflammatory response in the target tissue. Since skin is often involved in tissue injury, the present studies were designed to develop a model for assessing cutaneous peptide secretion as a marker for neurogenic inflammation in skin tissue. skin tissue. Calcitonin gene-related peptide (CGRP), as one of several neuropeptides known to be involved in neurogenic inflammation, was chosen to study capsaicin-induced effects on peripheral neurosecretion. The corial surface of the hairy skin of a rat hindlimb was superfused in vitro, and the basal and capsaicin-evoked peripheral release of immunoreactive CGRP (iCGRP) was measured using a radioimmunoassay, The main objectives of these studies were to characterize the various properties of this release including dose-dependency, exocytosis and receptor-mediation as well as the effects of acute and long-term capsaicin desensitization. Capsaicin significantly and dose-dependently increased the release of iCGRP at concentrations ranging from 3 to 300 mu M. Omission of calcium ions or treatment with the competitive capsaicin receptor antagonist capsazepine completely inhibited the capsaicin-induced iCGRP release. Superfusion of the skin with 100 mu M capsaicin following a conditioning stimulation with capsaicin at concentrations ranging from 0.3 to 100 mu M led to an acute, dose-dependent desensitization of the CGRP response. In addition, chronic desensitization following the neonatal injection of capsaicin completely abolished the acute iCGRP response to capsaicin. The method described here should prove to be a valuable tool for the evaluation of the processes regulating the peripheral, cutaneous release of pro-inflammatory neuropeptides. This strategy, therefore, may lead to a better understanding of the mechanisms involved in the development and maintenance of neurogenic inflammation, particularly in the skin. (C) 1997 International Association for the Study of Pain. Published by Elsevier Science B.V.
Keywords: CGRP; skin; neurogenic inflammation

Potentiation of evoked calcitonin gene-related peptide release from oral mucosa: a potential basis for the pro-inflammatory effects of nicotine - Dussor, Gregory O; Leong, Anthony S; Gracia, Nicholas B; Kilo, Sonja; Price, Theodore J.; Hargreaves, Ken M; Flores, Christopher M. (European Journal of Neuroscience, 2003)
Inflammation of the buccal mucosa, gingiva and periodontal tissues is a significant problem in users of nicotine-containing tobacco products; however, the potential role of nicotine in the development of this inflammation is unclear. In many tissues, nicotine, acting through nicotinic acetylcholine receptors (nAChRs), has been shown to increase the release of the pro-inflammatory mediator calcitonin gene-related peptide (CGRP) thereby potentially contributing to neurogenic inflammation. The purpose of the present studies was to determine the effects of nicotine and other nAChR agonists on capsaicin-evoked immunoreactive CGRP (iCGRP) release from rat buccal mucosa and to identify a potential cellular basis for these effects. Using a previously validated model of in vitro superfusion, we show that the nAChR agonists nicotine (EC(50) 557 muM), epibatidine (EC(50) 317 pM) and cytisine (EC(50) 4.83 nM) potentiated capsaicin-evoked iCGRP release in a concentration-dependent manner by 123, 70 and 76%, respectively. The expression and distribution patterns of the mRNA transcripts encoding the alpha3, alpha4 and alpha6 nAChR subunits and their colocalization with CGRP and the capsaicin receptor VR1 were examined in rat trigeminal ganglion using combined in situ hybridization and immunohistofluorescence. Of all trigeminal neurons counted, mRNA encoding the alpha3, alpha4 and alpha6 subunits was found, respectively, in 14.45, 9.2 and 19.21% of neurons. The cell body diameter of most neurons containing any nAChR subunit was in the 30-40 mum range with slightly fewer in the 20-30 mum range. Co-localization of these alpha subunit transcripts with either CGRP or VR1 immunoreactivity ranged from approximately 5 to 7% for alpha4 and over 8% for alpha3 to 18% for alpha6. These data support the hypothesis that nicotinic agents, acting at nAChRs contained on primary sensory neurons, are capable of directly modulating the stimulated release of iCGRP. In the case of users of nicotine-containing tobacco products, this modulation could contribute to inflammatory processes within the oral cavity.
Keywords: buccal mucosa; capsaicin; cytisine; epibatidine; nicotinic acetylcholine receptor; sensory neuron

Reflections on the OECD guidelines for in vitro skin absorption studies - Hopf, Nancy B.; Champmartin, Catherine; Schenk, Linda; Berthet, Aurelie; Chedik, Lisa; Du Plessis, Johan L.; Franken, Anja; Frasch, H. Frederic; Gaskin, Sharyn; Johanson, Gunnar; Julander, Anneli; Kasting, Gerald B.; et al. (Regulatory Toxicology and Pharmacology, 2020)
At the 8th conference of Occupational and Environmental Exposure of the Skin to Chemicals (OEESC) (16–18 September 2019) in Dublin, Ireland, several researchers performing skin permeation assays convened to discuss in vitro skin permeability experiments. We, along with other colleagues, all of us hands-on skin permeation researchers, present here the results from our discussions on the available OECD guidelines. The discussions were especially focused on three OECD skin absorption documents, including a recent revision of one: i) OECD Guidance Document 28 (GD28) for the conduct of skin absorption studies (OECD, 2004), ii) Test Guideline 428 (TGD428) for measuring skin absorption of chemical in vitro (OECD, 2004), and iii) OECD Guidance Notes 156 (GN156) on dermal absorption issued in 2011 (OECD, 2011). GN156 (OECD, 2019) is currently under review but not finalized. A mutual concern was that these guidance documents do not comprehensively address methodological issues or the performance of the test, which might be partially due to the years needed to finalize and update OECD documents with new skin research evidence. Here, we summarize the numerous factors that can influence skin permeation and its measurement, and where guidance on several of these are omitted and often not discussed in published articles. We propose several improvements of these guidelines, which would contribute in harmonizing future in vitro skin permeation experiment
Keywords: Skin absorption Skin permeation Percutaneous permeation In vitro skin permeation tests OECD guideline 428 Diffusion cell Chemical skin absorption Time lag Skin permeation coefficient

Systemic Diseases by Absorption Through the Skin - Drexler, Hans; Kilo, Sonja (Kanerva’s Occupational Dermatology, 2019)

The contribution of sensory nerves to the cutaneous microcirculation in patients with type 1 and type 2 diabetes - Kilo, Sonja; Berghoff, Martin; Hilz, Max-Josef; Freeman, Roy L. (1999)

UNRESPONSIVE AFFERENT NERVE-FIBERS IN THE SURAL NERVE OF THE RAT - Handwerker, Hermann Otto; Kilo, Sonja; Reeh, Peter (The Journal of Physiology, 1991)
1. The proportion of primary afferent nerve fibres in a skin nerve of the rat that responded or failed to respond to mechanical or thermal stimulation of the skin in the noxious and non-noxious range was analysed.2. Activity of afferent nerve fibres was recorded from the dorsal roots. Units projecting into the sural nerve were selected using supramaximal electrical stimulation of the nerve stem. All other hindleg nerves were cut.3. The receptive fields were searched by carefully examining the hindleg skin with noxious and innocuous mechanical, cooling and warming stimuli. Probing of the intrinsic foot muscles and manipulation of the ankle and toe joints was employed to recruit units projecting to deeper tissues.4. In a first series of twenty-two experiments, eighty-nine rapidly conducting myelinated A-beta units, thirty slowly conducting myelinated A-sigma units and 101 unmyelinated C units were investigated. Most units were identified as belonging to one of the established classes of cutaneous sensory units and this was also ascertained by a collision test.5. Two A-beta, eight A-sigma and forty-six C fibres did not respond to any one of the stimuli. Electrical thresholds and conduction velocities of the unresponsive C fibres were not significantly different from those of the units responding to natural stimulation of their receptive fields. In the A-sigma group unresponsive and high threshold mechanoreceptive units were preferentially found among the units with the slowest conduction velocities.6. In a second series of seven experiments, one single nerve filament containing responsive and unresponsive C fibres was tested repetitively at 30 min intervals. Twenty unresponsive units and seven units responding to noxious mechanical and/or heat stimuli were studied. Ten of the twenty initially unresponsive units became activated by mechanical and/or heat stimuli after observation times of 30-150 min. Some of these units had mechanical thresholds as low as 64 mN (tested with calibrated von Frey hairs), or thermal thresholds down to 42-degrees-C.7. Two of the ten C units which became responsive in the course of an experiment later lost their responsiveness again. On the other hand, two of the C units which were initially responsive to noxious heat and/or noxious mechanical stimuli became completely unresponsive after repetitive stimulation, whereas one unit initially only responding to noxious heat became responsive to mechanical stimuli, suggesting that mechanical and heat responsiveness may be separately gained or lost by sensory C fibres.8. We conclude that a large proportion of afferent C and A-sigma units innervating the hairy skin of rat are insensitive to acute physical stimuli under physiological conditions. At least some of these units may be sensitized under more long-lasting perturbations of the tissue, notably in inflammation, and thus may contribute to inflammatory pain.

Validity of different biomonitoring parameters for the assessment of occupational exposure to N,N-dimethylformamide (DMF) - Seitz, Mirjam; Kilo, Sonja; Eckert, Elisabeth; Mueller, Johannes; Drexler, Hans; Göen, Thomas (Archives of Toxicology, 2018)
This study was performed to assess the relation between occupational exposure to N,N-dimethylformamide after an 8 h work shift in the acrylic fibre industry and its three biological markers N-methylformamide (NMFtotal), N-acetyl-S-(N-methylcarbamoyl)cysteine (AMCC), and N-methylcarbamoyl adduct at haemoglobin (MCVal). External DMF exposure of 220 workers was determined during the whole shift. A standardised questionnaire was used to obtain information about the worker's general health status, medical treatment, smoking habits, protective measures, and possible symptoms caused by DMF exposure. NMF and AMCC were analysed in post-shift urine samples and MCVal in blood. For longitudinal assessment the average AMCC concentration was determined over a period of 4 weeks (weekly sampling) in a sub-collective of 89 workers. The median of DMF concentration in air was 3.19 mg/m3 (range < 0.15-46.9 mg/m3). The biological markers showed a median of 4.80 mg/L (range 0.20-50.6 mg/L) for NMFtotal, 4.75 mg/g creatinine (range 0.06-49.6 mg/g creatinine) for AMCC, and 57.5 nmol/g globin (range 0.5-414 nmol/g) for MCVal. A significant linear relationship was observed between DMF in air and NMF as well as between DMF in air and AMCC in post-shift urine samples. The mean AMCC values measured weekly over a period of 4 weeks correlated significantly with MCVal adducts too. Excluding workers who had been using breathing masks on the day of the study led to even tighter correlations. The results of the present study demonstrate the applicability of the DMF biomonitoring parameters NMFtotal in post-shift urine for the present-day exposure assessment, AMCC in the post-shift urine after several shifts for assessment of the cumulative exposure of the previous working days, and MCVal for assessment of long-term exposure during previous weeks and months. The data of the present study enable now the estimation of valid equivalents of these biomonitoring parameters to the external DMF exposure. From the risk assessment point of view, the exposure limit values for AMCC and MCVal, which are directly linked to the presumed toxic intermediate MIC, exhibit a significant advance.
EVALuna2:34674

Vascular and neural mechanisms of ACh-mediated vasodilation in the forearm cutaneous microcirculation - Berghoff, Martin; Kathpal, Madeera; Kilo, Sonja; Hilz, Max-Josef; Freeman, Roy L. (Journal of Applied Physiology, 2002)
The relative contribution of endothelial vasodilating factors to acetylcholine (ACh) mediated vasodilation in the forearm cutaneous microcirculation is unclear. The aims of this study were to investigate the contributions of prostanoids and cutaneous C fibers to basal cutaneous blood flow (CuBF) and ACh-mediated vasodilation. ACh was iontophoresed into the forearm, and cutaneous perfusion was measured by laser-Doppler flowmetry. To inhibit the production of prostanoids, four doses of acetylsalicylic acid (ASA; 81, 648, 972, and 1,944 mg) were administered orally. Cutaneous nerve fibers were blocked with topical anesthesia. Cyclooxygenase inhibition did not change basal CuBF or endothelium-mediated vasodilation to ACh. In contrast, ASA (972 and 1,944 mg) significantly reduced the C-fiber-mediated axon reflex in a dose-dependent fashion. Blockade of C-fiber function significantly reduced axon reflex-mediated vasodilation but did not affect basal CuBF or endothelium-dependent vasodilation. The findings suggest that prostanoids do not contribute significantly to basal CuBF or endothelium-dependent vasodilation in the forearm microcirculation. In contrast, prostanoids are mediators of the ACh-provoked axon reflex.
Keywords: endothelium; prostaglandin; nitric oxide; axon reflex; acetylcholine